Whiteness and negrophilia: the consumption of the other in education of race and ethnic relations - Wellington Oliveira dos Santos (Universidade Federal de Santa Catarina, 2019)
This essay aims to propose the use of the term negrophilia (ARCHER-STRAW, 2000) in analyses on whiteness. Whiteness privilege allows white people to intentionally consume the history, the culture and the bodies of black people using the politically correct discourse without renouncing to their privileges, and these attitudes consist in negrophilia. First, the origin and use of the term, which is situated in early twentieth-century France, is presented, as can be found in studies on whiteness. In the second part of this essay, a case study is presented that illustrates how negrophilia is present in the educational system of Brazilian teachers' education and training, even though there is training directed at the education of ethnic-racial relations. The text argues that this can be noticed in the training of teachers for the education of race and ethnic relations, as well as in discourses that supposedly defend race and ethnic diversity.